2016
DOI: 10.1002/ejp.936
|View full text |Cite
|
Sign up to set email alerts
|

Threat and fear of pain induces attentional bias to pain words: An eye‐tracking study

Abstract: Interventions that change attention towards pain to reduce vigilance and subsequent avoidance may be indicated to improve pain outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 48 publications
4
47
0
1
Order By: Relevance
“…For example, Sharpe et al () found that although acute pain patients exhibited a bias towards sensory pain words, it was the avoidance of affective pain words that predicted chronicity three and six months’ later. Two recent laboratory studies have also highlighted the role of avoidance to affective pain words (Brookes, Sharpe, and Dear, ; Sharpe et al, ). For this reason, we also examined the duration of first fixation on affective pain words as a moderator of the relative efficacy of mindfulness versus distraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sharpe et al () found that although acute pain patients exhibited a bias towards sensory pain words, it was the avoidance of affective pain words that predicted chronicity three and six months’ later. Two recent laboratory studies have also highlighted the role of avoidance to affective pain words (Brookes, Sharpe, and Dear, ; Sharpe et al, ). For this reason, we also examined the duration of first fixation on affective pain words as a moderator of the relative efficacy of mindfulness versus distraction.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental attentional bias paradigm was a replication of a previous study using the same eye tracking methodology (Sharpe et al, ). The experimental word stimuli for the dot probe task were developed by Dehghani (Dehghani, Sharpe, and Nicholas, ) and consisted of 10 sensory pain and 10 affective pain words, each matched to a neutral word of equal length and frequency.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in eyetracking studies the duration of the first fixation was 206 ms (Todd et al, 2016) to 246 ms (Sharpe et al, 2017). Therefore, these results should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, it was biases away from affective pain words, that predicted chronicity both 3 and 6 months later (Sharpe et al, 2014).The threat interpretation model makes the prediction that under high threat the exact pattern of vigilance-avoidance found here will emerge. Nonetheless, the view that avoidance may be the putative attentional response to pain-related material has been supported by a number of recent eye tracking studies (Yang et al, 2012(Yang et al, , 2013Vervoort et al, 2013a;Heathcote et al, 2017;Sharpe et al, 2017;Todd et al, 2016). Nonetheless, the view that avoidance may be the putative attentional response to pain-related material has been supported by a number of recent eye tracking studies (Yang et al, 2012(Yang et al, , 2013Vervoort et al, 2013a;Heathcote et al, 2017;Sharpe et al, 2017;Todd et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation